Analisis Pengaruh Produk Domestik Regional Bruto UpahMinimum Kota Indeks Pembangunan Manusia Jumlah PendudukDan Beban/Tanggungan Penduduk Terhadap TingkatPengangguran Terbuka Di Kota-Kota Provinsi Jawa TimurTahun 2010 - 2015 - Sari, Dewi Kartika; , Drs. Triyono. M.Si (2017)
This study aimed to analyze the effect of the Gross Regional DomesticProduct (GDP), Minimum Wage Cities, Human evelopment Index, Populationand Expenses / Dependent Population against Unemployment Rate in Cities ofEast Java Province 2010-2015. This study uses secondary data and analytical toolsused in this research is the analysis of panel data regression. Data used in the formof time-series data (2010-2015) and a cross-section / cross-point (9 Cities in EastJava). The results showed that the Random Effect Model (REM) is a panel data regression model the best. Based on F test variables Gross Regional DomesticProduct (GDP), Minimum Wage Cities, Human Development Index, Populationand Expenses / Dependent Population simultaneously or jointly affect theUnemployment Rate in Cities in East Java province. Based on test validity influence (t test) showed that the variables of Gross Domestic Product (GDP) haspositive and not significant to the Unemployment Rate, variable Minimum ageCitiessignificant negative effect on the Unemployment Rate, variable Human Development Index is negative and not significant against Unemployment rate,the variable Population significant negative effect on the Unemployment rate andthe variable expenses / Dependents Population significant negative effect on theUnemployment rate in Cities in East Java province